PERGESERAN HALMAHERA EDDY KAITANNYA DENGAN PRODUKTIVITAS TANGKAPAN IKAN CAKALANG DI PERAIRAN SEKITARNYA - Harsono, Gentio; Supartono, Supartono; Manurung, D; Atmadipoera, Agus S; Syamsudin, Fadlt; Baskoro, Mulyono S (Jurnal Teknologi Perikanan dan Kelautan, 2015)
The water between Mindanao and New Guinea is one of areas fisheries potential skipjack (Katsuwanus pelamis) most advanced in the western pacific. The main of fisheries industry this type of dominated by purse-seine by large size (50-100 Gross Tonnage). The role of a Halmahera Eddy is very importance in the dynamics of fisheries in the region, but there is no that explain it yet. Data series arrest skipjack catch per unit of effort (CPUE) of Western Central Pacific Fisheries Commission (WCPFC) for a decade the period July 2002-December 2012 analyzed in order to see the relationship between shifting Halmahera Eddy with the productivity skipjack in the study areas. The results show that the productivity skipjack in the study areas correlates strongly against a meridional shifting of Halmahera Eddy where CPUE showing an increase in skipjack with lag time on two months after Halmahera Eddy center shifted to the north. While to zonal shifting have a correlation in which weak.